The Importance of Education in Preventing Mental Disorders Among Adolescents: A Study at SMA Muhammadiyah 4 Yogyakarta - Evi Ni'matuzzakiyah (Journal of Educational Innovation and Public Health, 2025)
Adolescent mental health is an important issue in the world. In Indonesia, the prevalence of mental disorders in adolescents is still high, but awareness of prevention and treatment is relatively low. This research aims to analyze the influence of knowledge on behavior to prevent mental disorders in students at SMA Muhammadiyah 4 Yogyakarta. The research uses quantitative methods with a pre-test and post-test design without a control group (one group pre-test post-test design). Education is provided in the form of counseling, followed by measuring the level of knowledge and behavior before and after the intervention. Data analysis was carried out using the Wilcoxon test with SPSS software. The results showed a significant increase in post-test scores compared to pre-test (significant value = 0.011). Effective education increases students' awareness and preventive behavior towards mental disorders. Therefore, mental health education programs need to be implemented on an ongoing basis to create a mentally and emotionally healthy generation.